From Caristi’s Theorem to Ekeland’s Variational Principle in 0σ-Complete Metric-Like Spaces - Mohamed Jleli; Bessem Samet; Calogero Vetro; Francesca Vetro (Abstract and Applied Analysis)
We discuss the extension of some fundamental results in nonlinear analysis to the setting of 0σ-complete metric-like spaces. Then, we show that these extensions can be obtained via the corresponding results in standard metric spaces.